y-6-7-(y-5)+5(6y+1)=

Simple and best practice solution for y-6-7-(y-5)+5(6y+1)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for y-6-7-(y-5)+5(6y+1)= equation:


Simplifying
y + -6 + -7 + -1(y + -5) + 5(6y + 1) = 0

Reorder the terms:
y + -6 + -7 + -1(-5 + y) + 5(6y + 1) = 0
y + -6 + -7 + (-5 * -1 + y * -1) + 5(6y + 1) = 0
y + -6 + -7 + (5 + -1y) + 5(6y + 1) = 0

Reorder the terms:
y + -6 + -7 + 5 + -1y + 5(1 + 6y) = 0
y + -6 + -7 + 5 + -1y + (1 * 5 + 6y * 5) = 0
y + -6 + -7 + 5 + -1y + (5 + 30y) = 0

Reorder the terms:
-6 + -7 + 5 + 5 + y + -1y + 30y = 0

Combine like terms: -6 + -7 = -13
-13 + 5 + 5 + y + -1y + 30y = 0

Combine like terms: -13 + 5 = -8
-8 + 5 + y + -1y + 30y = 0

Combine like terms: -8 + 5 = -3
-3 + y + -1y + 30y = 0

Combine like terms: y + -1y = 0
-3 + 0 + 30y = 0
-3 + 30y = 0

Solving
-3 + 30y = 0

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '3' to each side of the equation.
-3 + 3 + 30y = 0 + 3

Combine like terms: -3 + 3 = 0
0 + 30y = 0 + 3
30y = 0 + 3

Combine like terms: 0 + 3 = 3
30y = 3

Divide each side by '30'.
y = 0.1

Simplifying
y = 0.1

See similar equations:

| 100=10x-650+50 | | a+(3b-1)=2b+2 | | 8(2x-6)=2(8x+5) | | 3+7p-1=7p+22-4p | | -2x+10=28 | | -2x+10=20 | | 10-3[4(a+5)-3a]= | | -11.8x=70.8 | | 9y=-36 | | -5(2b+4)+(11b-6)=0 | | y=4E-41e^2x | | 5.1q-2.3-5.7q=-1.6q-2.9 | | g^2+6g-27=0 | | -3x+9+4x=10 | | r-13=-39 | | -(5y+2)-(-4y-8)=-1 | | 11z+9=9+11z | | (x^2+4)-(5x^2-3x+4)+(2x-3)=0 | | 8(3x-1)=2(12x+5) | | 2x+15=2x+16 | | 3+6t-2=8t+7-5t | | 84x^2+48y^2=0 | | 30=6y | | 23+(-8)+22-(-12)+8= | | (4m^2-6)(4m^2+6)= | | 4x+3=x+1 | | 3y+6y=72 | | 3.8q-4.9-4.8=-2.0q-4.7 | | 6w+5=-(5w+7) | | x-12+2x+6=6x+84 | | q-8=-17 | | y^2+8y=0 |

Equations solver categories